USE OF PUBLIC-PRIVATE PARTNERSHIP FOR DEVELOPMENT OF INFRASTRUCTURE - Igor Viktorovich Linev (Модернизация, инновация, развитие, 2016)
Need of research and introduction of innovative mechanisms of growth of economy of Russia in the conditions of the accruing crisis tendencies and external restrictions causes relevance of consideration of close interaction and mutually providing production and social infrastructures of the economic development forming additional eff ects in all variety of branches of industrial complex. Formation becomes the initiating factor of such interaction in modern conditions and eff ective use of domestic enterprise potential a necessary condition of which is state – private partnership (PPP). In this regard it is necessary to consider problems and problems of formation of conditions, forms and methods of use of PPP, for development of infrastructure as necessary complex of BasicElements of formation of advanced socially oriented market economy. As an object of research in article the organizational and economic relations assuming eff ective partnership of the government and private institutions for formation of complete and highly eff ective system of the production and social infrastructure causing an intensifi cation of synergetic and multiplicative eff ects of development of a civilized society are considered. Purposes/tasks. The main objective of a statement of materials in this article consists in theoretical justifi cation of basic provisions of realization of PPP in system of production and social infrastructure. The task to prove need of application of PPP for strengthening of multiplicative eff ect at development of this system is set. Methodology. In the methodological plan this work represents the state-of-the-art review of the social and economic processes happening in system of social and production infrastructure. When writing article the complex of general scientifi c methods of research including generalization, economical and statistical, system and analytical cluster and others was applied Results. As a result of performance of this work it is possible to draw a conclusion that production and social infrastructures interacting, form synergetic and multiplicative eff ects. Use of PPP can be considered as the mechanism establishing interaction of infrastructure links (production and social) and strengthening these eff ects. Conclusions/importance. Practical application of results of this work will allow to use eff ectively PPP in branches of production and social infrastructure. Use of this mechanism has the system gearing-up character as promotes achievement of the double duplicating eff ect in all other branches and spheres of economy and society. It is advisable to carry out transition from consideration of development of branches in pure form, to introduction of interaction of production and social infrastructures. The eff ect which isn't seen by cursory examination, in case of deeply studying, positioning of his emergence as functioning of system with positive feedback, can give a powerful impulse of development of economy of a national economy in general. The exit to new quality of economy of infrastructure sectors (as a result - on new production) causes as the end result, new quality of life support.